2009
DOI: 10.1002/ppap.200932208
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of TiO2‐Based Layer on Textile Substrate: Theoretical and Experimental Study

Abstract: This paper is aimed on both the experimental and the theoretical study of textile surface modification by the plasma‐enhanced chemical vapour deposition (PECVD). In the first part of this paper we describe experimental measurements of the layer profile that is deposited on the surface of a textile thread. The SEM photos of the TiO2‐based layer on fibres showed that the layer thickness changes significantly with the location of the fibre in the fabric. Although both the layer thickness and its profile are cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Considering that the highest increase in hydrophobicity was observed after plasma treatment in oxygen-containing process gas, oxidation processes with actively involved oxygen appear to play an important role in the formation of hydrophobic functional groups on the cellulose surface. Presented results correspond to our previous studies [ 66 , 78 , 79 ] and the findings reported in [ 80 ] that noble gases, such as argon, show a reduced capability in HMDSO dissociation compared to oxygen.…”
Section: Resultssupporting
confidence: 92%
“…Considering that the highest increase in hydrophobicity was observed after plasma treatment in oxygen-containing process gas, oxidation processes with actively involved oxygen appear to play an important role in the formation of hydrophobic functional groups on the cellulose surface. Presented results correspond to our previous studies [ 66 , 78 , 79 ] and the findings reported in [ 80 ] that noble gases, such as argon, show a reduced capability in HMDSO dissociation compared to oxygen.…”
Section: Resultssupporting
confidence: 92%
“…The warp interlacing angle Φ can be expressed from Equation (4) as in Reference [ 23 ], given here as Equation (5): where M is the spacing of yarns, r is the radius of yarns, and d is the height of cylinder of yarns.…”
Section: Methodsmentioning
confidence: 99%
“…PVD techniques have been used to produce protective coatings such as corrosion-resistant and wear-resistant coatings and coatings for sensor applications [7,8]. Textile functionalities obtained include electrically conductive, optical, magnetic and biocompatible materials for a wide range of applications [7,17,18].…”
Section: Physical Vapor Deposition (Pvd)mentioning
confidence: 99%